Presidential Control and Turnover in Regulatory Personnel. Issue 10 (November 2019) - Doherty, Kathleen M.; Lewis, David E.; Limbocker, Scott
Career executives often occupy administrative positions that determine the pace and content of policy, such as those responsible for developing regulations. Yet, presidential administrations need control over these positions to achieve policy aims. This article considers the extent to which new presidential administrations marginalize career executives in key regulatory positions by transferring responsibilities to another individual and whether the mere expectation of political conflict with a new administration drives career regulators from their positions. Using unique new data on 866 career regulators that led major rulemaking efforts between 1995 and 2013, we demonstrate that turnover among career executives in key regulatory positions increases following a party change in the White House. Turnover also increases during a presidential election year, but this effect is conditioned by bureaucrats' expectations of the election outcome. Finally, career executives are more likely to depart in response to favorable labor market conditions. Given our findings that turnover in regulatory responsibilities is driven both by presidential marginalization and strategic exit by bureaucrats, we conclude with implications for presidential efforts to control the administrative state.